Secondary osteoporosis prevention: three‑year outcomes from a Fracture Liaison Service in elderly hip fracture patients - González-Quevedo, David; Rubia-Ortega, Carolina; Sánchez-Delgado, Adriana; Moriel-Garceso, Diego; Sánchez-Siles, Juan Manuel; Bravo-Bardají, Manuel Francisco; García-de-Quevedo-Puerta, David; Tamimi-Mariño, Iskandar Ahmad (Springer, 2024)
Hip fractures are the most serious fragility fractures due to their associated disability, higher hospitalization costs and high mortality rates. Fracture Liaison Service (FLS) programs have enhanced the management of osteoporosis-related fractures and have shown their clinical effectiveness. To analyze the effect of the implementation of a FLS model of care over the survival and mortality rates following a hip fracture. We conducted a prospective cohort study on patients over 60 years of age who suffered a hip fracture before and after the implementation of the FLS in our center (between January 2016 and December 2019). Patients were followed for three years after the index date. Mortality, complications and refracture rates were compared between the two groups using a Multivariate Cox proportional hazard model. The implementation of a FLS protocol was associated with a lower all-cause one-year mortality rate and a higher survivorship in elderly hip fracture patients. However, no three-year mortality rate differences were observed between the two groups. We also found a reduction in the complication and second-fracture rates.
Keywords: Osteoporosis; Cadera - Fracturas; Fracture liaison service; Hip fractures; Osteoporosis; Mortality; Re-fracture.